Quality Assurance in China: The Changing Context - Mohrman, Kathryn (International Higher Education, 2011)
Since 2003, China has assessed undergraduate education at hundreds of campuses. The overall result has been greater attention to and investment in teaching by the universities involved, although experience has identified some shortcomings in the process. The Ministry of Education has addressed some of these problem areas, including vague indicators, data fraud, and a "one size fits all" approach that was inappropriate for some institutions. Overall, the process demonstrates both decentralization and the continuing involvement of the central government.